2007
DOI: 10.1093/jee/100.2.327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus thuringiensis Transgenic Corn on Corn Earworm and Fall Armyworm (Lepidoptera: Noctuidae) Densities

Abstract: We examined 17 pairs of near-isogenic hybrids of Bacillus thuringiensis (Bt) (176, Mon810, and Bt11) and non-Bt corn, Zea mays L., to examine the effects of Bt on larval densities of Helicoverpa zea (Boddie) and Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) during 2 yr. During ear formation, instar densities of H. zea and S. frugiperda were recorded for each hybrid. We found that H. zea first, second, and fifth instar densities were each affected by Mon810 and Bt11 Bt corn but not by 176 corn. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Other studies involving cannibalism and intraguild predation of this species in the presence of Bt protein (Cry1Ab) in maize indicated reduced survival of H. zea in late instars on Bt maize, which decreases the regular rates of cannibalism and the H. zea -S. frugiperda intraguild predation of late instars on early instars. A reduction in cannibalistic behavior of H. zea might increase the survival of larvae in multiple infestations of Bt maize ears (Chilcutt et al 2007). Negative effects of Cry1Ab protein in H. zea behavior were also observed in an intraguild interaction study involving this species, Striacosta albicosta (Smith) (Lepidoptera: Noctuidae), and Ostrinia nubilalis (Hübner) (Lepidoptera: Noctuidae) (Dorhout and Rice 2010).…”
Section: Discussionmentioning
confidence: 92%
“…Other studies involving cannibalism and intraguild predation of this species in the presence of Bt protein (Cry1Ab) in maize indicated reduced survival of H. zea in late instars on Bt maize, which decreases the regular rates of cannibalism and the H. zea -S. frugiperda intraguild predation of late instars on early instars. A reduction in cannibalistic behavior of H. zea might increase the survival of larvae in multiple infestations of Bt maize ears (Chilcutt et al 2007). Negative effects of Cry1Ab protein in H. zea behavior were also observed in an intraguild interaction study involving this species, Striacosta albicosta (Smith) (Lepidoptera: Noctuidae), and Ostrinia nubilalis (Hübner) (Lepidoptera: Noctuidae) (Dorhout and Rice 2010).…”
Section: Discussionmentioning
confidence: 92%
“…This was demonstrated by Chilcutt and Tabashnik (2004), where kernels of non-Bt plants in an adjacent refuge area near Bt11 and Mon810-expressing plants, had Cry1Ab toxin concentrations that were 45 and 43% less than the adjacent Bt11 and Mon810 plants, respectively. For H. zea, corn plants with Bt11 and Mon810 events expressing Cry1Ab toxin do not provide a high dose, deÞned as a 25ϫ higher dose than is necessary to provide 99% mortality of the most susceptible life stage in a laboratory bioassay; this is true even with maximum Cry1Ab expression in the ear, allowing larval survival on ear tips (Horner et al 2003, OÕRourke and Hutchison 2004, Chilcutt et al 2007). Subsequently, even higher levels of survival are observed under the cross-pollination scenario (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…it should not be surprising that some levels of cross-resistance could exist between Cry1F and Cry1A.105 because of the association in the gene structures of the 2 proteins. Studies have shown that S. frugiperda was somewhat tolerant to the single gene Cry1Ab corn hybrids (US EPA 2001b;Chilcutt et al 2007;Hardke et al 2011;Huang et al 2011). In addition, Cry1Ac usually shares similar binding sites with Cry1Ab in the insect midgut membranes (Ballester et al 1999;Ferré & Van Rie 2002;Hua et al 2001;Tan 2010) and thus Cry1Ab resistance is often found to be cross-resistant to Cry1Ac in many insect species (Tabashnik et al 1994;Ferré &Van Rie, 2002;Rang et al 2004;Siqueira et al 2004;Wu et al 2009;Pereira et al 2010;Tan 2010;Crespo et al 2011;Zhang et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Fall armyworm, Spodoptera frugiperda (J. E. Smith), is an important pest of corn in both North and South America (Pashley et al 1985;Pashley 1986;Buntin et al 2004;Chilcutt et al 2007). Several studies have evaluated the field efficacy of first generation single gene Bt corn products (e.g.…”
mentioning
confidence: 99%